Financial performance of banking sector: the role of board gender diversity as a moderating factor - Bagiana, I Kadek; Putra, M. Doni Permana; Putri, Yura Karlinda Wiasa; Dewi, I Gusti Agung Mas Tika Purnama; Pebrianti, Ni Gusti Ayu Trisna (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose – This study examines the impact of the cost-to-income ratio (CIR), loan-to-deposit ratio (LDR), and capital adequacy ratio (CAR) on return on equity (ROE), with board gender diversity (BGD) as a moderating factor. Firm size (SIZE) and non-performing loans (NPL) are included as control variables. Method – A panel data regression approach using the fixed effect model (FEM) is applied, covering 47 banking companies listed on the Indonesia Stock Exchange (IDX) between 2021-2023, resulting in 141 observations. Findings – The findings show that CIR and LDR negatively affect ROE. CAR and SIZE positively affect ROE. BGD negatively affects ROE but strengthens the negative relationship between CIR, LDR, and ROE. However, BGD cannot moderate the relationship between CAR and ROE. NPL shows do not affect ROE. Implications – These results have important implications for banking management and regulators, emphasizing the need for strategies to enhance operational efficiency, improve liquidity risk management, and strengthen governance through gender diversity on boards. The theoretical implications of this study suggest that gender diversity on boards can improve strategic decision-making and risk management. From a practical standpoint, the insights are particularly relevant to the banking sector in Indonesia, where such practices can contribute to both improved financial performance and sustainable governance.